Comparative risk-benefit profiles of weak opioids in the treatment of osteoarthritis: a network meta-analysis of randomized controlled trials. Issue 8 (17th November 2022) - Li, Wei; He, Hongyi; Yang, Zidan; Wu, Ziying; Xie, Dongxing
ABSTRACT: Background: Despite their poor tolerance, weak opioids are still the most commonly-prescribed medicine for osteoarthritis (OA)-related pain. The objective of this network meta-analysis was to comparatively examine the efficacy and safety of weak opioids in OA treatment. Methods: Databases including PubMed, Embase, Cochrane Library and Web of Science were searched from inception to 4 April 2022 to retrieve randomized controlled trials (RCTs) comparing weak opioids with placebo or between one another in OA patients. Bayesian network meta-analysis was performed on the following outcomes of interest, namely the change-from-baseline score in pain relief, gastrointestinal (GI) adverse events (AEs), central nervous system (CNS) AEs, and total number of AEs (i.e. the number of subjects experiencing any AE for at least once) during follow-up. The surface under the cumulative ranking curve (SUCRA) was used to rank the effectiveness of each treatment and identify the best treatment. Results: A total of 14 RCTs invoving four types of weak opioids were included in this meta-analysis. Compared to placebo, tramadol (standardized mean difference [SMD] = −0.34, 95% credible interval [CrI]: −0.53 to −0.18) and codeine (SMD = −0.39, 95% CrI: −0.79 to −0.04) were effective for pain relief, but involved a higher risk of GI AEs, CNS AEs and total number of AEs. Dextropropoxyphene demonstrated a significantly lower risk of GI AEs (OR = 0.28, 95%CrI: 0.17 to 0.51), CNS AEs (OR = 0.29, 95%CrI: 0.11 to 0.78) and total number of AEs (OR = 0.35, 95%CrI: 0.15 to 0.82) compared to codeine. Dihydrocodeine had a better safety profile in CNS AEs (SUCRA = 64.8%) and total number of AEs (SUCRA = 66.6%). Conclusions: The results of the present study confirmed that tramadol and codeine were effective drugs for the treatment of OA, but involved considerable safety issues. Dextropropoxyphene and dihydrocodeine exhibited a relatively good safety profile but their efficacy still warrant further investigation.